PENGARUH EDUKASI GIZI BERBASIS MEDIA VIDEO DAN LEAFLET TERHADAP PENGETAHUAN GIZI SEIMBANG SISWA SMPN 14 KOTA BEKASI - Nirma Marcelina Zares (2020)
The most cause of nutrition problems in adolescents is due to lack of nutritional knowledge and lead to a wrong choice of what meals would be consumed because the level of knowledge in adolescents. Nutrition education is highly important to encourage adolescent nutrition knowledge so it is necessary to be socialized as an effort to change the wrong eating habits. This study aimed to see the impact of nutrition education by using video and leaflet on student knowledge. This type of research is a quasi-experiment used a one-group pretest-posttest design. The number of samples were 88 students. The average pre-test of the video group was 59.31 and the post-test was 72.05 with a standard deviation is 14.40. While in the leaflet group the pre-test average was 69.77, and the post-test was 82.95 with a standard deviation is 15.01. Results of the Paired Sample T-Test analyzed is 0,000 < 0.05 for video. And p-value 0.003 < 0.05 for the leaflet, which means there is an impact of nutrition education used video and leaflets on balanced nutrition knowledge of 14th JHS Bekasi Students. The result of Independent T-Test is leaflet more effective as a nutrition education media.